2023
DOI: 10.3390/app13042510
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Microstructural Studies of High Performance Concrete with Condensed Silica Fume

Abstract: This article is an extended version of the conference paper “Influence of silica fume on mechanical and fracture properties of high performance concrete” published in Procedia Structural Integrity as a part of the Special Issue for the 3rd International Conference on Structural Integrity (ICSI 2019). Tests were carried out to evaluate the compressive strength, tensile splitting strength, modulus of elasticity, flexural strength, and fracture properties of high performance concretes (HPC) having different level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…The value of the Ca/Si ratio presented in Table 3 reflects the favorable pozzolanic reaction rate. These results confirm the active role of silica fume in strengthening the microstructure of HPC without the addition of CKD [49]. Based on these results, it can be seen that the percentage of calcium in the HPC mixture with 20% CKD is higher than in the reference mixture, which indicates a quicker setting time in HPC with cement dust.…”
Section: Microstructuresupporting
confidence: 71%
“…The value of the Ca/Si ratio presented in Table 3 reflects the favorable pozzolanic reaction rate. These results confirm the active role of silica fume in strengthening the microstructure of HPC without the addition of CKD [49]. Based on these results, it can be seen that the percentage of calcium in the HPC mixture with 20% CKD is higher than in the reference mixture, which indicates a quicker setting time in HPC with cement dust.…”
Section: Microstructuresupporting
confidence: 71%
“…For the MD simulations, LJ and coulombic short-range interactions were cut off at 1.0 nm. Long-range interactions were computed using the Particle Mesh Ewald summation with a 0.16 nm grid spacing and fourth-order interpolation [20,21]. The V-rescale method was utilized to maintain the temperature, and the Berendsen pressure coupling method was implemented to maintain system pressure.…”
Section: Classical All-atom Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Anish et al (2022) explored the synergistic effects of fly ash and silica fume in concrete, demonstrating improvements in strength and durability, especially when combined with superplasticizers [19]. Smarzewski (2019) reported that condensed silica fume could enhance the mechanical properties of high-performance concrete, particularly tensile strength and fracture energy, though the optimal replacement levels should not exceed 20% [20]. Lastly, Khan et al (2022) investigated binary cementitious systems incorporating silica fume and micro-quartz filler, finding that these materials significantly reduce porosity and permeability while enhancing compressive strength [21].…”
Section: Introductionmentioning
confidence: 99%
“…Concrete has several advantageous characteristics, including high wear resistance, low water permeability, and good compressive strength, and it is widely used in civil structures [15][16][17][18]. To maintain resident safety and structure durability, construction engineers are mainly concerned with the quality of building materials, notably the compressive strength of concrete.…”
Section: Literature Reviewmentioning
confidence: 99%